Non-suicidal self-injury in inpatient and outpatient adolescents: disentangling psychopathology and interactive family dynamics - Fasolato, Rachele; Raffagnato, Alessia; Miscioscia, Marina; Gatta, Michela (Frontiers in Psychiatry, 2025)
BackgroundNon-suicidal self-injury (NSSI) is defined as a transdiagnostic phenomenon that has well increased in the latest years, especially in the adolescent population. It has been associated with suicidality, alexithymia, emotion dysregulation, and psychosocial impairment, as well as family issues. The choice of level of care (i.e., hospitalization versus outpatient visit) depends on a number of factors that relate not only to suicidal risk but also to severity of individual’s psychosocial functioning, the ability of family environment to support treatment choices and to contain child, as well as the need for ongoing monitoring of the young patient. A scarcity of studies has compared outpatients with inpatients, both of them engaging in NSSI.Methodsthe current study aimed to further expand knowledge regarding features that characterize young self-harmers who receive different levels of care, with particular attention on psychopathological, family, and NSSI-related characteristics, as well as suicidality. The current research included 56 inpatients and 56 outpatients with NSSI, paired for gender, age, and psychiatric diagnosis. Instruments investigating psychopathology, emotion dysregulation, alexithymia, psychosocial functioning, and interactive family dynamics were administered. Descriptive statistics, parametric and non-parametric inferential statistics were applied.Resultsstudy findings highlighted that inpatients engaging in NSSI reported lifetime suicidality, clinical level of externalizing and internalizing problems, more severe alexithymia, emotion dysregulation, and impaired psychosocial functioning compared to outpatients engaging in self-harming. Furthermore, when compared to outpatients’ families, inpatients’ families were more capable of adhering to rules and time of the family play situation (the Lausanne Trilogue Play procedure) and fixing interactive mistakes through activities. On the contrary, in the inpatient group, global performance, role implication, parental scaffolding, child’s involvement and self regulation tend to decline, while parental conflicts tend to rise over the four part scenario of the family play.Conclusionthese findings confirmed a more severe global picture of young inpatients engaging in self-harming, suggesting that NSSI may be the expression of this larger psychopathological picture. In addition, the study highlighted the need for a multi-informant and multimethod clinical assessment, which should include evaluation of family context and co-parenting system, especially for hospitalized young patients engaging in self-harm.